RESOLUSI JIHAD : NASIONALISME KAUM SANTRI MENUJU INDONESIA MERDEKA - Saputra, Inggar (JURNAL ISLAM NUSANTARA, 2019)
Nahdlatul Ulama is an Islamic-nationalist organization that has many important roles in achieving Indonesian independence. One of the contributions of this organization is present in Jihad Resolution. Jihad resolution was born as an answer to the uncertainty that hit the Indonesian leaders in facing the invaders. Through Jihad Resolution, the santri and freedom fighters succeeded in defeating Allied forces from Indonesia. Jihad resolutions which generally contain two categories of jihad. First, fardhu ‘ain it is for everyone who is within a 94 km radius of the epicenter of occupation of the invaders. Second, fardlu kifayah for residents who are outside the radius. However, under certain conditions and emergencies, the status can be increased to fardhu ‘ain. Jihad resolution is considered as a strategic decision and of great value in providing moral support to the nation's leaders and igniting the patriotism of the santri, the people and the ulama in the physical revolution against the invaders. The clerics left the pesantren, leading the resistance to the last drop and gave command in front of the santri. Jihad Resolution is a manifesto of the nationalism of Indonesian clerics and clerics in upholding the building of Indonesian independence that the nation's founding fathers have just built. The existence of this fatwa signifies how kyai and santri not only understand religious issues, but also master national problems and play an active role in providing strategic solutions to existing problems. There are two strategic impacts on the resolution of jihad for the life of the nation and state. First, affirming the sovereignty of Indonesia as an independent nation from all forms of invaders in the Indonesian homeland. Second, united the unity of the warriors in a row to win independence and in the future gave birth to the Indonesian National Army.